Norwegian Scabies management after prolonged disease course: A case report - Aukerman, William (Int J Surg Case Rep, 2019)
INTRODUCTION: Scabies is a well – known, commonly recognized, and frequently diagnosed pathology especially in children, close quarters, living facilities, and immunocompromised patients. An accelerated severe infestation of traditional scabies with limited treatment options is known as the rare entity of Norwegian or Crusted Scabies. CASE PRESENTATION: We present the history, clinical manifestations, medical treatments and surgical interventions of a patient with Norwegian Scabies of his hands, which rendered them nonfunctional prior to intervention. The patient was initially misdiagnosed and underwent inappropriate treatments for several years prior to our assessment, and ultimately required surgical intervention that was therapeutic. DISCUSSION: Norwegian, or Crusted, Scabies is a severe infestation of S. scabiei in which the mite load is extreme in comparison to traditional scabies. This manifests as scaly plaques that are often misdiagnosed for other hyperkeratotic skin lesions. With this misdiagnosis, improper treatments are often recommended, and can even accelerate the manifestation. Traditional scabies therapies can be effective, however often due significant disease progression due to diagnostic delay, invasive measures, such as surgical debridement like presented here, are the only option. CONCLUSION: The patient presented in this case harbored a rare infection, known as Norwegian Scabies, for several years, with inappropriate medical therapy. Due to his prolonged inadequate treatments, his disease became so pronounced that the recommended medical treatments were no longer adequate, thus he required surgical debridements which ultimately allowed him to regain function in his hands.